Systematic Review on the Incidence of Bisphosphonate Related Osteonecrosis of the Jaw in Children Diagnosed with Osteogenesis Imperfecta - Anusha Adeline Hennedige; Jap Jayasinghe; Janette Khajeh; Tatiana V. Macfarlane (eJournal of Oral Maxillofacial Research)
Objectives: To conduct a systematic review of epidemiological literature to determine the incidence of bisphosphonate related osteonecrosis of the jaw occurring either spontaneously or after dental surgery, in children and adolescents diagnosed with osteogenesis imperfecta.